Assessing and managing the shift work disorder in healthcare workers - d’Ettorre, Gabriele (Med Lav, 2018)
BACKGROUND: Shift work disorder (SWD) is a major concern for both healthcare workers (HCWs) employed in hospital wards and healthcare organizations. The consequences of SWD may lead to increased service costs and lower standards of care. OBJECTIVES: To identify and evaluate the latest developments in assessing and managing the occupational risk of SWD in shift-HCWs through a search of the literature published in the last five years. METHODS: We performed a search of the literature starting from June 2012, using MEDLINE/Pubmed. The articles were reviewed and categorized into one or more of the following categories based on their subject matter: Risk assessment, Risk management, Occurrence rates. RESULTS: A total of 25 publications matched the inclusion criteria. The topics discussed, in order of frequency (from the highest to the lowest), were: “Risk Assessment” (84%), “Occurrence Rates” (64%) and “Risk Management” (48%). Number of nights worked per year, long night-time working hours, frequent missing of nap opportunities during night-shift, quick returns and unhealthy workplace were found as organizational determinants of SWD that should be prioritized in the risk assessment of shift work in the healthcare sector. CONCLUSIONS: Organizational interventions targeted on both healthy shift-work scheduling and improvement of the workplace safety are proposed to moderate the occurrence of SWD and, consequently, to ensure HCWs’ wellness and suitable standards of patient care. Further studies aimed to investigate the effectiveness of such interventions in minimizing SWD occurrence are needed.